Separation Of Inheritance Assets And Its Implications In Indonesian Civil Law - Silaen, Riama Novalia; Sembiring, Tamaulina Br. (PT. Anagata Sembagi Education, 2024)
This research employs qualitative methods with a literature study approach to explore the legal phenomenon of inheritance separation in Indonesian civil law. The approach involves collecting, reviewing, and analyzing relevant literary sources, including books, journal articles, regulations, and court decisions. The initial step is identifying and collecting relevant literature, followed by an analysis to understand basic concepts, legal principles, and procedures. Researchers critically analyze the collected literature to identify key issues, challenges, debates, and evaluate each source's relevance and validity. Findings indicate that inherited assets are significantly regulated by the Indonesian Civil Code. The Code addresses heirs' rights and obligations, inheritance separation procedures, and special conditions that must be met. The process aims to end joint ownership and distribute assets to each heir according to their rights, requiring all heirs' agreement or a court decision in case of disputes. Article 1075 regulates dispute resolution, allowing courts to intervene. Provisions for canceling inheritance separation protect heirs' rights, with Articles 1112 and 1116 providing a basis for cancellation if there is coercion, fraud, or actions harming more than a quarter of the inheritance value. Overall, Indonesian law offers comprehensive protection for heirs, ensuring the inheritance process aligns with justice and legal principles.